Aortic valve replacement with pulmonary hypertension: Meta‐analysis of 70 676 patients. Issue 12 (5th November 2019) - Rocha, Rodolfo V.; Friedrich, Jan O.; Hong, Kathryn; Lee, Jessica; Cheema, Asim; Bagai, Akshay; Verma, Subodh; Yanagawa, Bobby
Abstract: Background and Aim of the Study: We compared early and late outcomes of surgical aortic valve replacement (SAVR) in patients with aortic stenosis (AS) and pulmonary hypertension (PHT). Methods: We searched MEDLINE and EMBASE databases until July 2018 for studies comparing patients with AS and none, mild‐moderate, or severe PHT undergoing SAVR. Random‐effects meta‐analysis was performed. Results: There were 12 observational studies with 70 676 patients with median follow‐up 4.0 years (interquartile range, 2.6‐4 years). Compared to patients with no PHT, patients with any PHT undergoing SAVR were older (mean difference [MD], 2.31 years; 95% confidence interval [CI], 1.38‐3.23 years; P < .01), with greater comorbidities and reduced ejection fraction (MD, −4.36; 95%CI, −5.94 to −2.78; P < .01). Patients with any PHT had higher unadjusted (5.2% vs 2.4%; risk ratio [RR], 2.27; 95%CI, 2.04‐2.53; P < .01) and adjusted (RR, 1.65; 95%CI, 1.28‐2.14; P < .01) in‐hospital mortality compared with no PHT. Severe (RR, 3.53; 95%CI, 1.46‐8.54; P < .01) and mild‐moderate PHT (RR, 2.13; 95%CI, 1.28‐3.55; P < .01) were associated with higher unadjusted in‐hospital mortality compared with no PHT. Any PHT was associated with a higher unadjusted risk of stroke (RR, 1.64; 95%CI, 1.42‐1.90; P < .01), acute kidney injury (RR, 2.02; 95%CI, 1.50‐2.72; P < .01), prolonged ventilation (RR, 1.62; 95%CI, 1.04‐2.52; P = .03), and longer hospital stay (MD, 1.76 days; 95%CI, 0.57‐2.95; P < .01). Severe (HR, 2.44; 95%CI, 1.60‐3.72; P < .01) but not mild‐moderate PHT (HR, 2.25; 95%CI, 0.91‐5.59; P = .08) was associated with higher adjusted long‐term mortality compared with no PHT. Conclusions: Patients with severe AS and severe PHT had a significant increase in operative mortality and more than double the risk of long‐term mortality following SAVR compared with patients with no PHT. Such patients may benefit from a less invasive transcatheter aortic valve intervention.